2013
DOI: 10.5702/massspectrometry.s0019
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Chemicals as Tracers of Atmospheric Sources and Fate Processes in a World of Changing Climate

Abstract: Elimination of persistent organic pollutants (POPs) under national and international regulations reduces "primary" emissions, but "secondary" emissions continue from residues deposited in soil, water, ice and vegetation during former years of usage. In a future, secondary source controlled world, POPs will follow the carbon cycle and biogeochemical processes will determine their transport, accumulation and fate. Climate change is likely to affect mobilisation of POPs through e.g., increased temperature, altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
0
12
0
2
Order By: Relevance
“…Mixed degradation, though largely of the (+) enantiomer, was found in the equatorial Indian Ocean (Huang et al, 2013). A compilation of degradation preferences for α-HCH in 270 agricultural and background soils showed that (−) degradation was favoured in 50 %, (+) degradation in 20 %, and 30 % contained racemic residues, with an overall mean EF of 0.528 ± 0.095 (reviewed by Bidleman et al, 2012Bidleman et al, , 2013. Regional "footprints" are important in determining the enantiomer composition of α-HCH in air.…”
Section: α-Hchmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed degradation, though largely of the (+) enantiomer, was found in the equatorial Indian Ocean (Huang et al, 2013). A compilation of degradation preferences for α-HCH in 270 agricultural and background soils showed that (−) degradation was favoured in 50 %, (+) degradation in 20 %, and 30 % contained racemic residues, with an overall mean EF of 0.528 ± 0.095 (reviewed by Bidleman et al, 2012Bidleman et al, , 2013. Regional "footprints" are important in determining the enantiomer composition of α-HCH in air.…”
Section: α-Hchmentioning
confidence: 99%
“…4) suggest that microbial processing plays a role in its transport and fate, but how and where is unclear. Average degradation preferences in soils worldwide are 56 % (+)TC, 29 % (−)TC, with 15 % of soils containing racemic TC; 22 % (+)CC, 64 % (−)CC, and 14 % racemic CC; and average EFs are TC 0.480 ± 0.067, and CC 0.531 ± 0.073 (reviewed by Bidleman et al, 2012Bidleman et al, , 2013. From these general enantiomer profiles, emissions from soils should be depleted in (+)TC and (−)CC.…”
Section: Chlordanesmentioning
confidence: 99%
“…Chiral pesticides, i.e., pesticides with at least two enantiomers which are non-superimposable mirror images of each other, may constitute more than 25% of currently used pesticides worldwide [1,2]. Enantiomers of chiral pesticides have identical physico-chemical properties, and transport processes or abiotic reactions appear not changing enantiomers proportions [3]. In contrast, degradation of chiral pesticides may be mainly microbiologically-mediated and enantioselective [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Söz konusu bu çalışmalarda, kiral bileşikler rasemik (henüz yeni kullanılmış veya bozunma proseslerinden etkilenmeden korunmuş) ve rasemik olmayan (mikrobiyal bozunmaya uğramış veya uzun süredir çevresel ortamda bulunan) oranları kullanılarak kirleticilerin taşınım mekanizmalarının ve akıbetlerinin değerlendirilebileceği öngörülmektedir [93], [102].…”
Section: Kiral Bileşiklerin çEvredeki Akıbetiunclassified